The Dynamics of Criminal Law Reform in Indonesia: a Historical and Prospective Review From the Colonial Penal Code to the 2023 National Criminal Code - Marnija, Marnija; Zainal Arifin Hoesein (Fox Justi : Jurnal Ilmu Hukum, 2025)
Criminal law reform is a fundamental agenda within Indonesia’s national legal system, particularly aimed at replacing the colonial legacy of the Wetboek van Strafrecht, which had remained in effect for over a century. This study aims to examine the dynamics of criminal law reform from the colonial era to the enactment of the 2023 National Criminal Code (KUHP), and to analyze the challenges of implementing this codification within the context of substantive law. The research adopts a normative juridical approach, utilizing literature review methods and qualitative analysis of both primary and secondary legal sources. The study employs historical, statutory, conceptual, and comparative approaches. The findings indicate that the 2023 KUHP represents a monumental achievement in the development of national law, as it is founded on the values of Pancasila, the principles of social justice, and respect for human rights. However, the substance of several articles remains repressive and open to multiple interpretations, failing to fully embody the principles of modern, responsive, and democratic criminal law. Furthermore, a significant gap exists between the idealism of codification and its practical application, as evidenced by the unpreparedness of law enforcement institutions, the lack of supporting instruments, and public resistance to controversial provisions such as articles on cohabitation, adultery, and defamation of state institutions. Therefore, criminal law reform in Indonesia must extend beyond normative changes and be accompanied by institutional reform, capacity-building for legal actors, and broader public participation.